Answer:
[tex]y = 3(x +21)[/tex]
Step-by-step explanation:
Find the inverse this equation:
[tex]f(x) = (\frac{1}{3}x) - 7[/tex]
-Take the variable [tex]y[/tex] for [tex]f(x)[/tex], because both
[tex]y = (\frac{1}{3}x) - 7[/tex]
-Switch both variable [tex]x[/tex] and [tex]y[/tex] :
[tex]y = (\frac{1}{3}x) - 7[/tex]
[tex]x = (\frac{1}{3}y) - 7[/tex]
-Solve for [tex]y[/tex] :
[tex]x = (\frac{1}{3}y) - 7[/tex]
-Switch sides:
[tex]\frac{1}{3}y - 7 = x[/tex]
-Add both side of the equation by [tex]7[/tex] :
[tex]\frac{1}{3}y - 7 + 7 = x + 7[/tex]
[tex]\frac{1}{3}y = x + 7[/tex]
-Multiply both sides by [tex]3[/tex] :
[tex]\frac{\frac{1}{3}y}{\frac{1}{3} } = \frac{x + 7}{\frac{1}{3} }[/tex]
[tex]y = \frac{x + 7}{\frac{1}{3} }[/tex]
-Divide [tex]x + 7[/tex] by multiplying by [tex]\frac{1}{3}[/tex]
[tex]y = \frac{x + 7}{\frac{1}{3} }[/tex]
[tex]y = 3(x +21)[/tex]
Therefore, the answer is [tex]y = 3(x +21)[/tex].